Animal Interrupted, or Why Accepting Pascal's Wager Might Be the Last Thing You Ever Do. (September 2014) - Baron, Sam; Van Dyke, Christina
Abstract: According to conventionalist accounts of personal identity, persons are constituted in part by practices and attitudes of certain sorts of care. In this paper, we concentrate on the most well‐developed and defended version of conventionalism currently on offer (namely, that proposed by David Braddon‐Mitchell, Caroline West, and Kristie Miller) and discuss how the conventionalist appears forced either (1) to accept arbitrariness concerning from which perspective to judge one's survival or (2) to maintain egalitarianism at the cost of making "transfiguring" decisions such as Pascal's Wager rationally intractable. We consider three ways the egalitarian conventionalist could make these choices tractable and show that each one comes at significant cost to the view. We end the paper by considering whether accepting arbitrariness would be a better move for the conventionalist and conclude that, even here, she runs the risk of transfiguring choices being rationally intractable.